What should we be recommending for the treatment of enteric fever? - Parry, CM; Qamar, FN; Rijal, S; McCann, N; Baker, S; Basnyat, B (Oxford University Press, 2023)
Patients with suspected enteric (typhoid and paratyphoid) fever are predominantly managed as outpatients in endemic regions. Nonspecific clinical presentation, lack of accurate diagnostic tools, and widespread antimicrobial resistance makes management challenging. Resistance has been described for all antimicrobials including chloramphenicol, amoxycillin, trimethoprim-sulfamethoxazole, ciprofloxacin, ceftriaxone, and azithromycin. No significant differences have been demonstrated between these antimicrobials in their ability to treat enteric fever in systematic reviews of randomized controlled trials (RCTs). Antimicrobial choice should be guided by local resistance patterns and national guidance. Extensively drug-resistant typhoid isolates require treatment with azithromycin and/or meropenem. Combining antimicrobials that target intracellular and extracellular typhoid bacteria is a strategy being explored in the Azithromycin and Cefixime in Typhoid Fever (ACT-SA) RCT, in progress in South Asia. Alternative antimicrobials, such as the oral carbapenem, tebipenem, need clinical evaluation. There is a paucity of evidence to guide the antimicrobial management of chronic fecal carriers.